Meningkatkan Efektivitas Pengelolaan Tenaga Pendidik di Sekolah Dasar - Tasya Dona Yuliany; Aulia Yessy Tri Wijayanti; Azzahra Vanya Stella Sadono; Yuliana Kayame; Lisa Virdinarti Putra (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2025)
Good teacher management is essential to improve the quality of education at the elementary level. This article focuses on the analysis of teacher management in elementary schools and presents ways to improve the effectiveness of that management. Efforts to improve the quality of education through teacher management can be considered as one of the determining factors for success or failure in education. Management can be understood as a process of arranging so that something that is managed can run smoothly, directed, effectively, and efficiently. In addition, management also includes the implementation of activities by utilizing all available resources, which have been planned to be implemented and evaluated periodically according to certain procedures in order to achieve the goals that have been set. To improve the effectiveness of teacher management, good planning is needed, selecting needs that are in accordance with school conditions, and sustainable development strategies. This development can be done through professional training, competency certification, observation of learning practices, academic supervision, and the provision of fair and balanced compensation. With mature and structured management, educators can carry out their functions well in creating a quality and competitive learning environment.